Pengaruh Konten Beauty Influencer TikTok Terhadap Pengetahuan Tata Rias Wajah Peserta Didik SMK PGRI 4 Pasuruan - Luftha Rudiyanto, Michelle Grezanda; Kecvara Pritasari, Octaverina; Kusstianti, Nia; Megasari, Dindy Sinta (Jurnal Tata Rias, 2025)
Abstract This study aims to investigate the impact of beauty influencer content on TikTok on increasing knowledge about makeup among students of SMK PGRI 4 Pasuruan and how students' attitudes towards the content. The background of this study is the rapid development of social media as an alternative in the learning process, especially in the field of makeup that is visual and practical. The method used is quantitative by implementing a pre-test and post-test through measuring learning outcomes. The number of subjects in this study was 36 students from the Skin and Hair Beauty study program. The data collection tool used was a questionnaire using a Likert scale and t-test. The research findings show a significant increase in knowledge about makeup after students accessed TikTok content from beauty influencers, as evidenced by the results of the paired sample t-test with a significance value of 0.000. Student responses to beauty influencer content on TikTok vary widely. On the one hand, this social media platform can be a very useful learning tool, encouraging interest in learning and facilitating access, as students can easily access various educational materials and resources through TikTok. It also helps students collaborate on assignments, exchange ideas, provide feedback, and encourage creativity in learning and conveying ideas. Several factors that support knowledge enhancement include the quality of content presentation, trust in the influencer, appropriate video length and format, and the relevance of the material to students' needs. Therefore, content on TikTok can be used as an effective supplementary medium for increasing knowledge about makeup. Various studies have shown that students respond positively to interactive learning media applications, particularly regarding their appearance and ease of use. Keywords: beauty influencer, TikTok, knowledge, make-up, learning media, student responses.